PENGARUH PENGGUNAAN BAHASA INDONESIA YANG BAIK DAN BENAR TERHADAP KEMAMPUAN KOMUNIKASI MAHASISWA PENDIDIKAN FISIKA - Agnes Angelina Simanullang; Eka Nababan; Firza Mutia; Krismis Nataluya Sinuraya; Nurul Azizah (STKIP Subang, 2026)
This study aimed to determine the effect of proper and correct Indonesian language use on the communication skills of Physics Education students at Universitas Negeri Medan. Data were collected through questionnaires distributed to 30 Physics Education students at Universitas Negeri Medan and analyzed using descriptive statistics and simple linear regression. The results showed a significant effect of proper and correct Indonesian language use on students’ communication skills with a significance value of 0.009 (<0.05). The coefficient of determination (R²) was 0.218, indicating that 21.8% of the variation in communication skills among Physics Education students at Universitas Negeri Medan could be explained by the proper and correct use of Indonesian.